2021
DOI: 10.5101/nbe.v13i3.p321-327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chromium Oxide Nanoparticles on Growth and Biofilm Formation of Persistence Klebsiella pneumoniae Isolates

Abstract: Bacterial persistence is recognized as a major cause of antibiotic therapy failure, causing biofilms and chronic intractable infections. The emergence of persisters in K. pneumoniae isolates has become a worldwide public health concern. Despite this clinical threat, currently, there are no viable means for eradicating K. pneumoniae persisters. In this project, chromium oxide (Cr 2 O 3 ) nanoparticles were synthesized by the photochemical method. The morphology, topographic and physical properties of nanosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The Vitek-2 system was used to identify and cultivate all of the isolates on Luria Bertani (LB, Difco Laboratories) agar plates or in LB broth at a temperature of 37 °C. Based on our previous study, we determined the Persister cell assay [20].…”
Section: Bacterial Isolates and Growth Conditionsmentioning
confidence: 99%
“…The Vitek-2 system was used to identify and cultivate all of the isolates on Luria Bertani (LB, Difco Laboratories) agar plates or in LB broth at a temperature of 37 °C. Based on our previous study, we determined the Persister cell assay [20].…”
Section: Bacterial Isolates and Growth Conditionsmentioning
confidence: 99%
“…bacterial persistence, we have the potential to reduce bacterial resistance to antibiotics and drugs, ultimately leading to improved outcomes in the treatment of chronic infections [24]. In this study, we examined the impact of ZnO and TiO 2 NPs on the biofilm formation and persister cells in K. pneumoniae.…”
Section: The Expression Level Of Mrkh Fimh Mazf and Luxs Genesmentioning
confidence: 99%
“…Many studies have recently shown the synergistic effect of silver nanoparticles and graphene nano-sheets against microorganisms, including MDR pathogenic bacteria of K. pneumoniae, P. aeruginosa, E. coli, and A. baumannii [126][127][128]. Another recent study [129], showed that chromium oxide nanoparticles (Cr 2 O 3 -NPs) have important applications in different fields due to their physical and chemical properties that depending on their shape and size. Chromium (Cr) is a transitional metal that can exist in different oxidation states.…”
Section: Control Of Heteroresistance and Persistent Bacteriamentioning
confidence: 99%